Trimetazidine Ameliorates Myocardial Metabolic Remodeling in Isoproterenol-Induced Rats Through Regulating Ketone Body Metabolism via Activating AMPK and PPAR α - Li, Huihui; Ma, Zhi; Zhai, Yajun; Lv, Chao; Yuan, Peng; Zhu, Feng; Wei, Liping; Li, Qi; Qi, Xin (Frontiers in Pharmacology, 2020)
Background Metabolic remodeling plays a vital role in the development of heart failure. The trimetazidine can optimize fatty acid and glucose oxidation via inhibition of long-chain 3-ketoacyl CoA thiolase in the heart. So, trimetazidine commonly used in cardiovascular therapy as a myocardial metabolic drug. This study was conducted to assess the effects and mechanisms of trimetazidine on ketone body metabolism in heart failure rats. Methods A rat model of heart failure was established by continuous subcutaneous injection of isoproterenol in 10 mg/kg/d. We examined body weight, heart weight index, and tested B-type natriuretic peptide by kit. We detected the structure and function of the heart. Hematoxylin-eosin staining and Masson’s trichrome staining was performed to assess myocardial tissue morphology. To evaluate apoptosis, we used Tunel staining. Metabolic substrate contents of glucose, free fatty acid, ketone bodies, lactic acid, and pyruvate and ATP levels in myocardial tissues were measured with the corresponding kit. We detected the levels of protein expressions related to myocardial substrate uptake and utilization by Western blot. Results Trimetazidine remarkably reduced the heart weight index and B-type natriuretic peptide levels. Besides, trimetazidine increased the level of blood pressure and decreased heart rate. Moreover, trimetazidine inhibited decreases in left ventricular ejection fraction and left ventricular fractional shortening. Further, trimetazidine decreased the levels of collagen volume fraction and promoted ATP production in myocardial tissues. Trimetazidine also reduced the levels of free fatty acid, ketone bodies, lactic acid, and increased glucose and pyruvate levels in myocardial tissues. Furthermore, trimetazidine markedly inhibited apoptosis. More importantly, the protein expression levels related to myocardial substrate uptake and utilization increased dramatically in the trimetazidine group. In particular, the protein expressions related to ketone body utilization were prominent. Conclusions Trimetazidine could attenuate metabolic remodeling and improve cardiac function in heart failure rats. The potential mechanism for the cardioprotective effect of trimetazidine may be highly associated with its regulation of adenosine monophosphate-activated protein kinase, and peroxisome proliferator activated receptor α expressions. Along with the regulation, myocardial substrate utilization was improved, especially the utilization of ketone bodies.